2019
DOI: 10.1088/1755-1315/388/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between effect of adding propolis and antibiotic in in broiler chickens on productive performance and carcass traits

Abstract: This study was conducted to Compare effect between addition of propolis and antibiotic in performance and carcass traits of broiler from 07/02/2018 until 20/03/2018. 135 one day old unsexed chicks (Ross, 308) were reared for 42 day, they distributed to three treatments, three replicates per treatment (15 birds in replicate). First treatment was control, the second treatment was adding 0.5 g antibiotic (Oxytetracyclin 20%)/1 kg feed, and the third treatment was adding 1 g propolis / 1 kg feed. The results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The lack of effect of the additives added to the feed can be explained by the appropriate experimental environment, the good management conditions, and the nutritional quality of the feed provided, as also reported by Paz et al (2010) and Araujo et al (2019). Alani, Alheeti, and Alani (2019), evaluating the use of propolis extract in intercropping or antibiotic substitution in broiler feeding, observed that the inclusion of propolis extract and residue did not interfere with the performance data evaluated. Shaddel-Tili, Eshratkhah, Kouzehgari, and Ghasemi-Sadabadi (2017) studying different levels of properly in the broiler diet, reported that the use of 2,000 ppm of propolis powder in the diet improved body weight gain, feed intake, feed conversion, and production index (p < 0.05), suggesting that this supplementation had a positive effect on animal performance.…”
Section: Resultsmentioning
confidence: 57%
“…The lack of effect of the additives added to the feed can be explained by the appropriate experimental environment, the good management conditions, and the nutritional quality of the feed provided, as also reported by Paz et al (2010) and Araujo et al (2019). Alani, Alheeti, and Alani (2019), evaluating the use of propolis extract in intercropping or antibiotic substitution in broiler feeding, observed that the inclusion of propolis extract and residue did not interfere with the performance data evaluated. Shaddel-Tili, Eshratkhah, Kouzehgari, and Ghasemi-Sadabadi (2017) studying different levels of properly in the broiler diet, reported that the use of 2,000 ppm of propolis powder in the diet improved body weight gain, feed intake, feed conversion, and production index (p < 0.05), suggesting that this supplementation had a positive effect on animal performance.…”
Section: Resultsmentioning
confidence: 57%
“…Honeycomb contains many kinds of residues of bee products, such as beeswax, cocoons, honey, pollen, propolis, and royal jelly, and has been recognized to have several physiological and biochemical properties, including antibacterial, antioxidant, antimutagenic, antitumor, anti-inflammatory, and bactericidal properties ( Gekker et al., 2005 ; Li et al., 2008 ; Alvarez-Suarez et al., 2010 ; Cheng et al., 2011 ; Astani et al., 2013 ; Talas et al., 2014 ; Zhao et al., 2015 ). These properties may be attributed to the active components in honeycombs, such as flavonoids, polysaccharides and polyphenols ( Alani et al., 2019 ). In recent years, with the large-scale development of apiculture, bee products have been widely used in livestock and poultry production.…”
Section: Introductionmentioning
confidence: 99%